Pendidikan Multikulturalisme dan Prospeknya di Indonesia - Slamet Panuntun; Asyrofi Aziz (Syntax Idea)
Multicultural education is a model expected to create peace and address the growing conflicts. The primary goal of multicultural education in this context is to foster attitudes of sympathy, respect, appreciation, and empathy towards followers of different religions and cultures. Importantly, this multicultural education strategy aims not only to make it easier for students to comprehend their lessons but also to increase their awareness and encourage them to behave in a humanistic, pluralistic, and democratic manner. This research employs a qualitative approach, involving the collection, analysis, and synthesis of relevant literature on multicultural education and its prospects in Indonesia. The researcher gathers academic publications, scientific journals, books, and other related sources to understand previous research, current issues, and developments in the field of multiculturalism in Indonesia. Interviews are conducted to obtain direct data from various stakeholders involved in multicultural education in Indonesia. Potential interview respondents include government officials, educators, educational institution administrators, students, and other community members engaged in multiculturalism issues. Surveys are used to collect data from a larger sample, such as teachers or students in various educational institutions in Indonesia. Surveys can provide broader insights into perceptions, attitudes, and understanding of multiculturalism, as well as its prospects within the education community. The results of the research indicate that to achieve the goals of multicultural education, the participation and support of teachers or professors, educational institutions, and other education policymakers are crucial. Multicultural education can be implemented if done with the concepts and limitations of Islamic Shariah.